2023
DOI: 10.1001/jamanetworkopen.2023.31617
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection, Hospitalization, and Mortality in Adults With and Without Cancer

Seyed M. Hosseini-Moghaddam,
Frances A. Shepherd,
Sarah Swayze
et al.

Abstract: ImportancePatients with cancer are at increased risk of SARS-CoV-2–associated adverse outcomes.ObjectiveTo determine the associations of tumor type with SARS-CoV-2 infection, hospitalization, intensive care unit (ICU) admission, and death.Design, Setting, and ParticipantsThis retrospective, population-based cohort study included community-dwelling adults aged at least 18 years in Ontario, Canada, ICES-linked provincial health databases from January 1, 2020, to November 30, 2021. Data were analyzed from Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…8 In most reports, patients with acute myeloid leukemia or any acute leukemia were affected by higher mortality following COVID-19 infection with respect to subjects with other hematologic malignancies [9][10][11][12] ; some other studies reported a higher mortality for patients with multiple myeloma. 13,14 However, the present report does not compare short-term mortality after COVID-19 infection between patients affected by different diseases. To investigate the impact of the pandemic at the population level, the change in mortality rate for each hematologic malignancy was assessed during the pandemic with respect to its pre-pandemic level.…”
Section: Resultsmentioning
confidence: 79%
“…8 In most reports, patients with acute myeloid leukemia or any acute leukemia were affected by higher mortality following COVID-19 infection with respect to subjects with other hematologic malignancies [9][10][11][12] ; some other studies reported a higher mortality for patients with multiple myeloma. 13,14 However, the present report does not compare short-term mortality after COVID-19 infection between patients affected by different diseases. To investigate the impact of the pandemic at the population level, the change in mortality rate for each hematologic malignancy was assessed during the pandemic with respect to its pre-pandemic level.…”
Section: Resultsmentioning
confidence: 79%